THE CHANGE OF BODY COMPOSITION OF INDIGENOUS RAMS ON DIFFERENT BODY WEIGHT AND FEEDING LEVEL - Setyawan, A.R.; Rianto, E.; Sunarso, S.; Setyaningsih, K.; Mahesti, G. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
The aim of this research was to investigate the influence of body weight and feeding level on the changeof body composition of indigenous ram. This research was expected to establish the efficient feeding levelto produce high growth rate and meat quality of ram in tropical environment. Sixteen rams with differentbody weight (BW) were divided into 2 groups, i.e. light BW (10 + 1.47 kg) and heavy BW (18 + 1.18 kg).The experimental design was Split Plot design with two factors. The main plot was body weight (light andheavy) and the sub plot was level of feeding (FL, 1x maintenance and 1.5 x maintenance). The parametersmeasured in this experiment were live weight gain and body composition. The results of this study showedthat body water, body protein and body fat were significantly higher (P<0.01) in heavy body weight (HBW)than those in light body weight (LBW), and was higher in 1.5xM than those 1xM. Ram of HW and LW hadsimilar change rate of physical composition. Ram given 1.5xM had higher rate of change of body fat andbody water than those given feed at maintenance level. It can be concluded that there was no interactionbetween BW and FL on the change of body water, body protein and body fat. Ram of HBW and LBW hadsimilar rate of change of physical composition. Level of feeding affected body water content, the higherlevel of feeding resulted in fatter ram, leading to less body water content.